Dentists and dental hygienists’ comprehension of HIV infection associated periodontal implications and management - Ahmed, Muzammil Moin (Frontiers in Public Health, 2024)
Background In an era wherein, persuasive evidence continues to witness the association between systemic and periodontal diseases, the absence of scientific data on dental professionals’ comprehension concerning the HIV infection and periodontal link is lamentably backward. Thus, the key objective of this research is to ascertain the extent of comprehension possessed by dentists and dental hygienists concerning periodontal implications and their management in HIV patients. Methods It is a quantitative cross-sectional survey employing a descriptive approach focusing on a specific cohort of dental professionals. The study setting featured an online platform for the distribution of concealed, closed-ended, structured questionnaire. The data was gathered for four sections: six comprehension statements about periodontal manifestations in HIV patients; fifteen comprehension statements about HIV patients’ periodontal management; eight familiarity statements about HIV management; and two educational statements about HIV. The comparisons of comprehension scores were drawn between variables such as specialties, age groups, and genders. Results The survey represented 468 dental professionals representing distinct dental specialties, with a mean age of 24.26 ± 7.53 years. The mean comprehension score for all groups of participants is 10.31 ± 9.34 (33.25%). The highest scores were recorded among those aged 31–40 (20.67 ± 8.31), followed by those aged 40+ (19.38 ± 9.39), 20–30 (9.53 ± 8.96), and under 20 (8.92 ± 8.57), at p < 0.001. The female participants (15.06 ± 12.2) exhibited substantially better scores in contrast to the male participants (8.74 ± 7.57). Periodontists (27.77 ± 3.08) comprehended most, then the oral medicine practitioners (25 ± 0). Dental hygiene students (5.52 ± 3.56) and hygienists (7.67 ± 9.72) comprehended the least. The scores for all four domains assessed were disappointingly low: knowledge about HIV-periodontal manifestations (2.81 ± 2.18), knowledge about management of periodontal diseases in HIV patients (3.73 ± 4.7), familiarity with periodontal care in HIV patients (2.87 ± 3.01), and education received about HIV and periodontal diseases (0.91 ± 0.66). Conclusion Dental professionals are notably incomprehensive, unfamiliar, and lacking in expertise in the realm of periodontal facets of HIV. The periodontists and oral medicine practitioners showed a substantial amount of comprehension, while the dental hygiene students and dental hygienists presented a conspicuously inadequate level of comprehension. The study outcome could potentially serve as an invaluable instrument for self-assessment by dental professionals and educators. HIV/AIDS ought not to persist as an unspoken taboo or disregarded subject within the dental field, particularly in periodontics, but rather should receive prominence in dental schools and professional development programs.